2019
DOI: 10.1002/ejoc.201900276
|View full text |Cite
|
Sign up to set email alerts
|

Copper‐ and Cobalt‐Catalyzed Syntheses of Thiophene‐Based Tertiary Amines

Abstract: Thienylzinc halides and related compounds prepared by deprotonation followed by transmetalation were used in copper‐catalyzed amination using N‐benzoyloxy secondary amines. By extending the reaction to 1,5‐naphthyridine, it was showed that the competitive dimer formation observed in the case of thiophenes was linked with the low stability of some thienylamines rather than homocoupling. Interestingly, thienylzinc halides and related compounds prepared by transmetalation of thienylmagnesium halides, either prepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 102 publications
0
9
0
Order By: Relevance
“…In the course of a study published recently, we observed that copper-catalyzed N,N-diarylation of thienylamines is possible by using an excess of aryl iodide in the presence of 1 equivalent of activated copper and 3 equivalents of base. 58 Hence, 2-aminobenzaldehyde (1) was similarly treated by the different iodoanisoles (2 equiv) at the reflux temperature of dibutyl ether until disappearance of the starting materials. The expected 2-(diarylamino)benzaldehydes 6b-d were isolated in 14 to 63% yield, as a result of side reactions/degradation taking place in the course of the second, more difficult Narylation step (Table 2, entries 1-3, left).…”
Section: Syntheses Of Acridonesmentioning
confidence: 99%
“…In the course of a study published recently, we observed that copper-catalyzed N,N-diarylation of thienylamines is possible by using an excess of aryl iodide in the presence of 1 equivalent of activated copper and 3 equivalents of base. 58 Hence, 2-aminobenzaldehyde (1) was similarly treated by the different iodoanisoles (2 equiv) at the reflux temperature of dibutyl ether until disappearance of the starting materials. The expected 2-(diarylamino)benzaldehydes 6b-d were isolated in 14 to 63% yield, as a result of side reactions/degradation taking place in the course of the second, more difficult Narylation step (Table 2, entries 1-3, left).…”
Section: Syntheses Of Acridonesmentioning
confidence: 99%
“…From 2018 to now, Knochel et al have reported several procedures for the coupling of O -benzoylhydroxylamines under cobalt catalysis. The authors first reported the use of ArZnCl·Mg­(OPiv) 2 ·LiCl complexes, referred as arylzinc pivalate and abbreviated “ArZn­(OPiv)” in such couplings . These complexes can be obtained by transmetalation of Grignard reagents with Zn­(OPiv) 2 .…”
Section: Umpolung Couplingsmentioning
confidence: 99%
“…This method was then expanded to thiophene-derived heteroarylzinc chloride reagents . These reagents were obtained by Mg insertion ( 14 ), halogen/Mg exchange ( 15 ) or deprotonation ( 16 ), followed by a transmetalation with ZnCl 2 .…”
Section: Umpolung Couplingsmentioning
confidence: 99%
“…Besides direct introduction of an amino group by a Chichibabin reaction [ 4 ], functionalization at C-4 can be achieved by a direct deprotometalation-amination reaction ( Scheme 22 ). This methodology appears complementary to access to several 4-amino substituted 1,5-naphthyridines 62a – c [ 54 ].…”
Section: Reactivity Of 15-naphthyridinesmentioning
confidence: 99%
“…Functionalization at C-4 of 1,5-naphthyridine heterocycle 2a can be achieved by a direct deprotometalation-amination reaction (vide supra, Scheme 22 ) or by an indirect amination. The latter method involves a previously deprotometalation-iodolysis substitution reaction to afford the intermediate 81 ( Scheme 29 ), which permitted the access to a variety of 4-amino substituted 1,5-naphthyridines 62 (previously prepared, vide supra, Scheme 22 ) [ 54 ].…”
Section: Reactivity Of 15-naphthyridinesmentioning
confidence: 99%